Auditor Competence and Audit Quality on Organizational Performance: The Moderating Role Of Extrinsic Rewards - Ichsanuddin Akbar; Rohsita Amalyah Rasyid; Syahrir; Arifin; Astil Harli Roslan (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study examines the effect of upper management support on audit quality and auditor competence, as well as their impact on organizational performance, with extrinsic rewards as a moderating variable. Methods: This research employs a quantitative, explanatory design using a cross-sectional approach. The study was conducted on 240 auditors in Southeast Sulawesi using a census method. Data were collected through structured questionnaires measured on a five-point Likert scale and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Results: The results show that upper management support has a positive and significant effect on audit quality and auditor competence. Furthermore, audit quality and auditor competence significantly influence organizational performance. However, extrinsic rewards do not moderate the relationships between audit quality and organizational performance, nor between auditor competence and organizational performance. Implications: These findings imply that organizational performance is more influenced by internal structural support and professional competence than external reward systems. Future research is suggested to explore other moderating variables to better explain performance improvement